BIALL and the Wider World. (June 2019) - Worley, Loyita
Abstract: In this article Loyita Worley describes the relationships between the British and Irish Association of Law Librarians (BIALL) and its fellow organisations around the world. She looks at the way that BIALL has promoted law librarianship internationally and mentions some of the activities of the Association including its recent project work in Sierra Leone, as well as noting a few reminiscences along the way.